2016
DOI: 10.1038/srep19952
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Quantum Sieving in Porous Graphene-like Carbon Nitride for Light Isotopes Separation

Abstract: Light isotopes separation, such as 3He/4He, H2/D2, H2/T2, etc., is crucial for various advanced technologies including isotope labeling, nuclear weapons, cryogenics and power generation. However, their nearly identical chemical properties made the separation challenging. The low productivity of the present isotopes separation approaches hinders the relevant applications. An efficient membrane with high performance for isotopes separation is quite appealing. Based on first-principles calculations, we theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
4
34
0
Order By: Relevance
“…2), the D 2 permeance Q ( D 2 ) and the kinetic selectivity S ( D 2 / H 2 ) 19, 21, 33, 34 . Unlike the case of helium isotopes 21, 33 , the ZPE correction leads to a lower barrier for D 2 than that for H 2 , and thus the larger quantum tunneling probability of D 2 .
Figure 2Quantum tunneling probability t ( E ) of hydrogen passing through the pore of C 2 N- h 2D membrane as a function of kinetic energy under different strains. The solid curves represent the quantum-mechanical transmission of H 2 and the dashed curves represents that of D 2 , respectively.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), the D 2 permeance Q ( D 2 ) and the kinetic selectivity S ( D 2 / H 2 ) 19, 21, 33, 34 . Unlike the case of helium isotopes 21, 33 , the ZPE correction leads to a lower barrier for D 2 than that for H 2 , and thus the larger quantum tunneling probability of D 2 .
Figure 2Quantum tunneling probability t ( E ) of hydrogen passing through the pore of C 2 N- h 2D membrane as a function of kinetic energy under different strains. The solid curves represent the quantum-mechanical transmission of H 2 and the dashed curves represents that of D 2 , respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…3 He) is more inclined to transmit through the membranes 1820 . In these systems, the interaction between the membrane and the guest isotopes can be tuned by applying tensile strain which modifies the pore size of the membrane, and highly efficient isotopes separation with optimized selectivity and permeance can be obtained 21 . It is noteworthy that the zero-point-energy (ZPE) of hydrogen in confined systems would affect the energy barrier on the diffusion pathway 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical reports have shown that the magnetism of the C 2 N monolayers can be tuned by transition‐metal embedding into the cavity of the porous C 2 N monolayer and carrier doping . Earlier reports have shown that the C 2 N monolayer is an excellent candidate for gas separation because of its uniformly distributed subnanometer pores with designable pore sizes . Furthermore, C 2 N has been employed for widespread applications such as single‐atom catalysts, hydrogen evolution reactions (HER), oxygen evolution reaction (OER) catalysts, and water desalination …”
Section: Introductionmentioning
confidence: 99%
“…Among these, graphitic carbon nitride (g-C 3 N 4 ) has been studied for a long time [22] and it can be used in many energy applications, such as hydrogen generation [23], efficient energy storage [24], and photocatalytic degradation of pollutants [25]. Nanoporous carbon nitride materials, such as the C 2 N monolayer [26], can be applied in gas separation [27][28][29] or water desalination [30]. The carbon nitride materials not only have a huge potential in applications but also exhibit many interesting physical effects, including QSH [31], quantum anomalous Hall (QAH) [32,33], and spin-polarization [34,35] effects.…”
Section: Introductionmentioning
confidence: 99%